THE ROLE OF THE CHEMICAL INDUSTRY IN THE MANUFACTURING INDUSTRY AND ITS RELATIONSHIP WITH OTHER SECTORS - Sharipova Saodat Ubaydullaevna (Scholar Express Journals, 2022)
This article analyzes the links between the chemical industry and other manufacturing industries. The role of the chemical industry in the manufacturing industry and in the economy of our country today was also discussed. The study then obtained the results of correlation-regression analysis and empirical analysis using the VIF-criterion, Jarque-Bera Statistic and Fisher criteria. The last part of the article presents proposals for the development of the chemical industry, as well as short-term forecast values.
Keywords: chemical industry; manufacturing industry; model; trend model